EM attack sensor: Concept, circuit, and design-automation methodology - Miura, Noriyuki; Fujimoto, Daisuke; Nagata, Makoto; Homma, Naofumi; Hayashi, Yuichi; Aoki, Takafumi (Proceedings - ACM IEEE Design Automation Conference, 2015)
A side-channel attack exploiting EM-field leakage from a cryptographic processor IC is an existing serious threat to our information society. EM radiation during the IC operation is captured by an EM probe and the correlation to the crypto processing is statistically analyzed to reveal the secret information although it is protected in a software (algorithm) domain. This paper presents a reactive hardware (implementation) domain countermeasure against this EM attack, namely EM attack sensor. An on-chip sensor coil detects EM probe approach and reacts to protect the secret information from the tamper attack. The sensor concept and low-cost digital circuit implementation are reviewed, and the detail of the design-automation methodology highly-compatible to standard EDA tools is presented. A small hardware overhead of the sensor is silicon-proven in an actual 0.18μm CMOS test-chip implementation together with a 128bit AES crypto core. The test-chip measurements demonstrate successful sensor operation against the actual EM probe attack.